ICOAIMS 2023 International Conference advances Mathematics and Statistics disciplines for tech-savvy community - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
KUANTAN, 22 August 2023 - A total of 116 participants were involved in the International Conference on Applied & Industrial Mathematics and Statistics (ICoAIMS) for 2023 which lasted for three days starting today until 24 August 2023.